1991
DOI: 10.1128/jvi.65.3.1578-1583.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of murine polyclonal antisera and monoclonal antibodies generated against intact and denatured human papillomavirus type 1 virions

Abstract: Human papillomavirus type 1 (HPV1) virions, both as intact virion particles (IVP) and as detergentdenatured virions (DDV), were used to prepare polyclonal antisera and monoclonal antibodies (MAbs) in BALB/c mice. Anti-IVP antiserum contained type-specific HPV1 L2-reactive antibodies and no detectable HPV1 Ll-reactive antibodies. Anti-IVP MAbs recognized a linear epitope between L2 amino acids 102 and 108 (PIDVVDP). Anti-DDV antiserum contained type-specific HPV1 Ll-reactive and HPV1 L2-reactive antibodies. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot were performed as described by Jenison et al (17,18). Murine monoclonal antibodies specific for lLl and 1L2 were obtained from David Baker at SUNY Stony Brook and have been characterized by Yaegashi et al (37). Immunofluorescent staining of HPV-1 Li and L2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot were performed as described by Jenison et al (17,18). Murine monoclonal antibodies specific for lLl and 1L2 were obtained from David Baker at SUNY Stony Brook and have been characterized by Yaegashi et al (37). Immunofluorescent staining of HPV-1 Li and L2.…”
Section: Methodsmentioning
confidence: 99%
“…Like simian virus 40 and polyomavirus (2,3,14,31), the capsomeres of bovine papillomavirus type 1 and HPV-1 have been shown to possess fivefold symmetry (4) and therefore are likely to be pentamers of the major capsid protein. The Li open reading frame encodes the major capsid protein, and studies with virions and other systems expressing Li have identified a protein with an electrophoretic mobility consistent with its predicted size of approximately 55 kDa (8,12,25,30,33,37). A minor capsid antigen is encoded by the L2 ORF that also specifies a protein of 55 kDa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of the corresponding VLPs in the composition of HPV vaccines has therefore to be considered. Both linear and conformational epitopes have been identified on the surface of HPV L1 VLPs [9,10,18,39,41,44]. It is now well established that conformational epitopes are responsible for neutralizing antibody production [7,14,21,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the initial studies of serologic response to HPV employed recombinant DNA methods to clone and express late region 1 (L1) or 2 (L2) proteins with bacterial fusion proteins (16,23,49,50). Recently, the predominant humoral response to HPV virions has been shown to be directed against conformationally dependent structures that were not duplicated in bacterial fusion systems (12,17).…”
mentioning
confidence: 99%